Systematics of glenohumoral and acromioclavicular arthritis - Seifarth, A.; Roemer, Frank (Radiologe, 2015)
A common risk factor for osteoarthritis (OA) of the glenohumeral joint is instability and is often observed as a sequel to dislocation. Altered biomechanics will ultimately result in joint degeneration including osteophyte development at the lower margin of the humerus, glenoidal cartilage loss and surface deformity. An OA of the glenohumeral joint is often coexistent with soft tissue derangement of the shoulder. In advanced stages defects of the rotator cuff and OA of the glenohumeral joint may accelerate disease progression. Degenerative changes of the acromioclavicular joint (AC joint) are commonly seen in older persons with only modest correlation with clinical symptoms. Symptomatic OA of the AC joint is often concomitantly observed with degenerative changes of the glenohumeral joint.Standard radiographs are the basis of a structural assessment of shoulder OA but lack correlation with clinical symptoms and are insensitive for the detection of early degenerative changes. Magnetic resonance imaging (MRI) provides increased sensitivity for the detection of cartilage defects and reveals relevant soft tissue changes, such as lesions of the glenoid labrum and capsuloligamentous structures, which are seen in conjunction with instability. It is also the method of choice to detect clinically relevant bone marrow edema-like lesions or synovial changes that are associated with symptomatic OA.Standard radiographs are not applicable for detection of early degenerative changes. Once OA is suspected clinically, MRI is the method of choice for further structural assessment. The administration of an intravenous contrast agent is useful for assessing synovitis, which commonly correlates with clinical disease manifestations. For preoperative and surgical planning of joint replacement, MRI or CT should be used.
EVALuna2:14547